2017
DOI: 10.3892/or.2017.5475
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA-125b-5p is involved in the pathogenesis of osteoarthritis by downregulating SYVN1

Abstract: Abstract. Osteoarthritis (OA) is a degenerative disease characterized by deterioration of articular cartilage. The aim of this study was to identify and characterize the expression of microRNA-125b-5p (miR-125b-5p) in normal and OA synovial cells, and to determine its role in OA pathogenesis. First, the levels of miR-125b-5p and synoviolin 1 (SYVN1) were detected among normal, mild OA and severe OA groups with the use of quantitative PCR. Computational analysis was used to search for the target of the miR-125b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Synoviolin 1 (SYVN1) was associated with ER stress, chronic inflammation, and vascular overgrowth in diabetic retinopathy (DR) [37,38]. Overexpression of miR-125b-5p was associated with the pathogenesis of osteoarthritis by down-regulation of SYVN1 [38], reflecting that SYVN1 was closely associated with OA. Besides, in our study, SYVN1 was first identified as a target of miR-34a-5p using RIP and luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Synoviolin 1 (SYVN1) was associated with ER stress, chronic inflammation, and vascular overgrowth in diabetic retinopathy (DR) [37,38]. Overexpression of miR-125b-5p was associated with the pathogenesis of osteoarthritis by down-regulation of SYVN1 [38], reflecting that SYVN1 was closely associated with OA. Besides, in our study, SYVN1 was first identified as a target of miR-34a-5p using RIP and luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, reduced miR-29 is also implicated in fibrogenesis of systemic sclerosis, an autoimmune rheumatic disease (109). miR-125b-5p expression increases with OA severity (110), and miR-125b-5p overexpression inhibits OA synovial cell proliferation and promotes apoptosis by targeting synoviolin (SYVN1), suggesting miR-125b-5p upregulation is an attempt to attenuate synovial hyperplasia and fibrosis (110). Thus, miR-29 family miRs and miR-125b-5p expression may be part of an effort to maintain normal synovial function rather than contribute to pathologic OA disease progression.…”
Section: Synovial Membrane Contribution To Joint Pathology Via Mirsmentioning
confidence: 99%
“…Refining our analysis only for the top five expressed miRNAs, miR-24-3p is shown to be involved in downregulating MMP1 and MMP13 expression by targeting senescence marker p16INK4a [75]. miR-125b-5p was shown to promote apoptosis of synovial cells through targeting synoviolin 1 [76]. miR-222-3p may significantly suppress apoptotic death in chondrocytes by down-regulating HDAC4 and MMP13 levels and reducing cartilage destruction [77].…”
Section: Discussionmentioning
confidence: 99%